Evaluation of coarse aggregate movement and contact unbalanced force during asphalt mixture compaction process based on discrete element method. (18th April 2022) - Zhu, Xuan; Qian, Guoping; Yu, Huanan; Yao, Ding; Shi, Changyun; Zhang, Chao
Highlights: The Marshall impact compaction (MIC) process of asphalt mixture was simulated through Discrete Element Method (DEM). The DEM model of asphalt mixture during MIC process based on the aggregate virtual database was constructed. The volumetrics evolution information of asphalt mixture specimen during MIC process was obtained. The coarse aggregates movement and contact unbalanced force were evaluated. Abstract: To evaluate the stability of asphalt mixture aggregate network and the mechanism of coarse aggregate movement of the asphalt mixture during the compaction process, the Marshall impact compaction (MIC) process of asphalt mixture was simulated through Discrete Element Method (DEM) and the new index of the coarse aggregate particles contact unbalance force was proposed. Firstly, the mechanical parameters of the asphalt mortar at the compaction temperature were calculated based on the time–temperature superposition principle and the Dynamic Mechanical Analysis (DMA) tests. Secondly, the aggregate morphology properties were collected with a 3D blue-ray scanner, and the virtual aggregate database and the DEM model of asphalt mixture during MIC process with aggregate morphology properties were constructed. Thirdly, the volumetrics evolution information of the asphalt mixture specimen was obtained, and the coarse aggregates movement and contact unbalanced force were evaluated. The results indicated that the vertical displacement of coarse aggregate particles of asphalt mixture was larger than horizontal displacement in the MIC process. The vertical displacement increased with the increment of the aggregate particles size, the reason was that the contact number and the vertical unbalance force increased with the increment of the aggregate particles size. The horizontal displacement and rotation angle of coarse aggregate shown similar trend during MIC process, both of them increased greatly during the initial compaction process and tended to remain stable after that, and the horizontal displacement and rotation angle increased with the decrement of the aggregate particles size. It also found that the particles sizes have an impact on the unbalance force distribution of coarse aggregate, and the unbalance force of coarse aggregate decreased with the increment of blows which indicated that the asphalt mixture tends to become stable with the effects of compaction. And the result also indicated that the aggregate location has an impact on the aggregate movement displacement and aggregate skeleton stability.